Strategic Planning for Management Information Systems - Ein-Dor, Phillip; Segev, Eli (Management Science, 1978)
This paper deals with strategic planning for management information systems. Specifically, those variables of the strategic plan which impact on the success or failure of MIS are identified, and propositions are formulated relating states of the variables to system conditions. The variables concerned are the system development strategy, the purpose of MIS, the priority scheme, functions assigned the system, goals, definitions of requirements and documentation of the strategic plan. Two factors predominate in determining the appropriateness of strategic plans for MIS explicitness (the degree to which the process is conscious, formal and documented) and situational fit (the degree to which the MIS is compatible with the specific organization and its members). It is concluded that there is no one optimal, strategic plan for MIS. Each organization must develop that strategy which best fits its particular situation.